Detection of pork in pastry products for halal verification via polymerase chain reaction (PCR) techniques - Mohd Yusop, Mohd Hazim; Che Man, Yaakob; Mustafa, Shuhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Pork identification in pastry fillings using polymerase chain reaction (PCR) was developed. Genomic DNA of the pastry filling were successfully extracted and found to be good quality and produced clear PCR products. In this study, two methods of PCR were used for detection of pork adulteration in several types of pastry fillings, including Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and species-specific PCR amplification. PCR amplification of mitochondrial cytochrome b gene (mt-cyt b) for PCR-RFLP produced DNA fragments of approximately 360 bp. This generated amplicons were then digested with restriction enzyme BsaJI, resulting in RFLP profiles of 228 bp and 131 bp in sizes which are specific for pork. Besides that, the species-specific PCR amplification of cyt b gene produced DNA fragments with approximate size of 398 bp as expected for the positive results. The findings from this study can serve as a basis of reference for the research in halal food authentication.